Spatio-temporal variability of temperature and chlorophyll-a concentration of sea surface in Bali Strait, Indonesia - Adi Wijaya; UMI ZAKIYAH; ABU BAKAR SAMBAH; DADUK SETYOHADI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wijaya A, Zakiyah U, Sambah AB, Setyohadi D. 2020. Spatio-temporal variability of temperature and chlorophyll-a concentration of sea surface in Bali Strait, Indonesia. Biodiversitas 21: 5283-5290. The Bali Strait is influenced by seasonal and inter-annual systems. El Nino-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) are climate variabilities that affect water conditions. The knowledge about influence of ENSO and IOD variations on the fertility of waters in the Bali Strait is still lacking. The purpose of this study was to determine the effect of seasonal and inter-annual variability on the variability of Sea Surface Temperature (SST) and Sea Surface Chlorophyll-a (SSC) in the Bali Strait. This study applied SST and SSC data collected from the Aqua/Terra MODIS satellite, as well as the ENSO and IOD indices during March 2000-December 2019. The results described that the effect of ENSO on SST and SSC was low and IOD on SST and SSC was quite high. The effect was quite high between IOD and SST anomaly of-0.401. Seasonal variations indicate the abundance of high SSC and low SST in the southeast monsoon (JJA) which characterizes upwelling. Meanwhile, in the northwest monsoon (DJF), SSC was low and SST was high which characterizes downwelling. This condition cannot separate from the monsoonal process that occurred in the Bali Strait. The inter-annual variation showed that in the strong El Nino period and IOD (+) triggers a negative SST anomaly and a positive SSC results in strong upwelling, while in the strong La Nina period and strong IOD (-) triggers a positive SST anomaly and a negative SSC results in downwelling. The inter-annual variability of SSC influenced by IOD rather than ENSO. This condition indicates that the ENSO/IOD event changes the period of SSC concentration.